Menghidupkan Kembali Pelabuhan Penyeberangan Danau Batur Menjadi Tempat Wisata Di Kintamani Bali - I Kadek Agus Berliana Arbi; I Nyoman Gede Maha Putra; I Wayan Widanan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Reviving the Lake Batur Crossing Port to Become a Tourist Place in Kintamani Bali is a redesign of the Kedisan Port facilities due to unorganized port conditions, minimal facilities, decreased visitors, underutilized natural potential of Lake Batur and other architectural problems that have resulted in the port not being interested in being visited. a decrease in the income of the community around the port. This design focuses on designing a ferry port with tourism and recreation which has several new facilities such as a restaurant, coffee shop, bar, public space, and recreation to play in the lake with natural potential and the beauty of the lake and Mount Batur which will revive the port area which has only been known so far. as a crossing only. With the concept of Port And Lake Tourism, which is an amalgamation of the port's function as a crossing transportation facility and a new port atmosphere with natural and culinary tourism, not only for ferry tourists but for local people and local tourists. With the application of neo vernacular architecture which has a spirit of innovation and tradition so that it can present new ideas with traditional values in it with a more modern and open architectural design that is close to nature so that visitors will feel at home for a long time in this port so that this can indirectly be achieved. increase the income of the surrounding community.